Characterization of Deposits in Calcific Tendinitis of the Shoulder: Deposits Are Composed of Large Aggregates of Highly Crystalline, Rod-Like Crystals. Issue 10 (11th October 2021) - Mateos, José Maria; Singer, Gad; Kaech, Andres; Ziegler, Urs; Eid, Karim
Background: In the current literature, deposits in calcific tendinitis are described as amorphous masses of hydroxyapatite with a size in the range of 5 to 20 μm. Theoretically, these are too big to be phagocytized by macrophages and induce an inflammatory reaction. Purpose: To better characterize the deposits seen in calcific tendinitis. Study Design: Case series; Level of evidence, 4. Methods: Included in the study were 6 patients with a history of at least 1 year of shoulder pain (range, 1-14 years). Shoulder arthroscopy was performed under general anesthesia, and calcium deposits from the supraspinatus tendon and biopsies from the adjacent subacromial bursa were taken. Samples were analyzed by light microscopy and immunostained for macrophages. Scanning electron microscopy and energy-dispersive x-ray (EDX) analysis were used to assess the morphology and chemical composition of the calcific deposits. Results: Light microscopy showed round and bulky calcium deposits partially surrounded by activated CD68-positive macrophages within inflammatory tissue. Some hemosiderin positive mononuclear cells, indicative for (micro-) hemorrhage, were seen. Scanning electron microscopy revealed that the large calcific deposits (1-20 μm) were composed of rod-like structures. These highly crystalline rods had a size of approximately 100 nm in length and 20 nm in width. Chemical composition by EDX analysis showed that crystals were composed of mainly calcium, oxygen, and phosphorus, equaling the chemical composition of hydroxyapatite. Conclusion: Deposits in calcific tendinitis of the rotator cuff are not amorphous but composed of highly crystalline structures. Fragmentation of these aggregates and subsequent release of the needle-like nanocrystals might initiate the strong inflammatory reaction often seen in patients with calcifying tendinitis of the rotator cuff.